Atlas of the heart [compact disc, unabridged] : mapping meaningful connection and the language of human experience - Brown, Brené (Random House Audio, 2022)
Brené Brown takes us on a journey through eighty-seven of the emotions and experiences that define what it means to be human. As she maps the necessary skills and an actionable framework for meaningful connection, she gives us the language and tools to access a universe of new choices and second chances, a universe where we can share and steward the stories of our bravest and most heartbreaking moments with one another in a way that builds connection.